Popper and Darwin: Bio-cosmological Evolutionism and Epistemological Evolutionist - Arana, Juan (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
The capacity to generalize is one of the more characteristic traits of Popper as philosopher. He proposes a Lamarckism without Lamarck, a vitalism without vitalist principles nor entelechies, and ananimism without soul. At bottom, Darwin did the same with teleology because of natural selection: He promoted a finalism without ends. The speculation is risky, but in some way, can be rejected. The problem with Popper is he sometimes does not know how to restrain himself and is too involved in first-rates cientific debates. Something similar happened to him with regard to discussions that followed the development of quantum mechanics: Instead of moving cautiously in the field of meta-theoretical reflection, he had to propose a «mental experiment» to mediate in the Einstein-Bohr controversy.
Keywords: Darwin; Popper; evolution; biocosmology; natural selection; determinism